Studie efektivnosti řízení zásob - Martináková, Jana (Vysoké učení technické v Brně. Fakulta podnikatelská, 2011)
Tato bakalářská práce se zaměřuje na studii řízení zásob ve výrobním podniku. V teoretické části práce jsou definována teoretická východiska práce zahrnující klasifikaci zásob, definici nákupu, skladování a řízení výroby. V praktické části práce je popsán současný stav v daném ekonomickém subjektu. Prostřednictvím aplikace ABC analýzy, analýzy obrátek zásob a dalších metod práce analyzuje zaběhnuté procesy a snaží se zvýšit jejich efektivnost.

The Bachelor´s thesis focuses on the study of effectiveness the inventory management in the manufacturing company. Basic terms such as inventory classification, purchasing, storage and production management are defined in the theoretical part of the thesis. The current inventory management in this particular economical subject is described in the practical part of the thesis. The Bachelor´s thesis analyses the established process that is currently used for the inventory management by using the ABC analysis, the analysis of the inventory turnovers and similar methods with goal to improve the effectiveness.
The Study of Effectiveness the Inventory Management
Keywords: zásoby; řízení zásob; ABC analýza; obrátky zásob; nákup; dodavatel; stocks; inventory management; ABC analysis; inventory turnovers; purchasing; supplier